PENGARUH LITERASI KEUANGAN DAN LITERASI DIGITAL TERHADAP KINERJA BERKELANJUTAN UMKM DENGAN PERSEPSI RISIKO SEBAGAI MEDIATOR - Randi Pakan; Aam Bastaman (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the influence of financial literacy and digital literacy on the sustainable performance of MSMEs, with risk perception as a mediating variable. The research background is based on the low levels of financial and digital literacy, which remain major obstacles to MSME development, particularly in Jakarta. The study employs a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The sample consists of 303 MSME actors selected through purposive sampling. The results reveal that financial literacy has a positive and significant effect on sustainable performance, although it does not significantly influence risk perception. In contrast, digital literacy significantly affects both sustainable performance and risk perception. Furthermore, risk perception is found to have a positive and significant effect on sustainable performance. Mediation testing indicates that risk perception does not mediate the effect of financial literacy on sustainable performance but does mediate the relationship between digital literacy and sustainable performance. These findings emphasize the importance of enhancing digital literacy accompanied by risk awareness to strengthen the competitiveness of MSMEs in the era of digital transformation. This research contributes theoretically to the study of literacy and risk management and provides practical implications for MSMEs, policymakers, and supporting institutions in designing sustainable empowerment strategies.